dalam, pada Peran Komik Strip “Proyek Molor” dalam Strategi Pemasaran Digital pada Perusahaan GoCement - Susandi, Natasha Audrey; Nuryadi (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2025)
The digital revolution has completely changed the way companies approach marketing, especially in industries such as construction that have traditionally relied on conventional methods. Since then, comic strips have been seen as an effective medium to build brand identity and connect with audiences. Their unique combination of visuals and storytelling cuts through the noise of digital content, making complex topics accessible and memorable. This study examines how GoCement, as a progressive construction platform, has integrated comic strips into its digital marketing strategy. Using Robin Landa's structured design approach, a five-stage process (orientation, analysis, conception, design and implementation) was used to create a comic strip that aligns with GoCement's brand values. The goal of the project was to increase engagement, with audiences not only interacting more frequently but also retaining brand messages for longer. Insights from this project show how a comic titled “Project Molor” can remind and educate readers how to use the GoCement app to avoid mistakes. This approach offers a way to balance education, promotion and entertainment, creating specialized content that appeals to both experts and newcomers. This strategy highlights the growing importance of creative visual storytelling in B2B marketing, where standing out and being remembered is just as important as consumer-facing campaigns.